STUDI KESESUAIAN LAHAN POHON SERBAGUNA (MPTS) DI KELURAHAN LAYANA INDAH, KECAMATAN MANTIKULORE, KOTA PALU - Taiyeb, Asgar (Wanamukti: Jurnal Penelitian Kehutanan, 2023)
This research was motivated by the aftermath of the land rehabilitation program with MPTS plants in the Mantikulore District by the Palu City Government. Closely related to efforts to determine land suitability classes for several types of MPTS in Layana Indah Village, Palu City. Land assessment, especially land suitability assessment, becomes important to prevent obstacles that may arise from limitations for plant growth, especially MPTS plants. The research was carried out for seven months, from April to September 2021, in Layana Indah Village, Mantikulore District, Palu City, Central Sulawesi. The field survey method was purposive sampling or carried out deliberately on other use areas in Palu City, Layana Village. Soil samples were taken from Wintu, representing Layana Village, another use area in the development of forest and land rehabilitation programs. In comparison, collecting climate data from the Meteorology and Geophysics Agency of Palu City. Land suitability assessment refers to the Atlas Format Procedure. Suitability indicators for several types of MPTS (durian, breadfruit, mango and jackfruit) are water availability, field slope, drainage, rock outcrops, and effective depth. The research in Layana Indah Sub-District shows the suitability of MPTS land with the limiting factor of dry months.